2015
DOI: 10.1136/vetreccr-2014-000146
|View full text |Cite
|
Sign up to set email alerts
|

Total excision of a caudal mediastinal paraoesophageal abscess in a dog

Abstract: A three-year-old female Irish setter dog presented with a history of shallow breathing, pyrexia and regurgitation. CT imaging revealed a 13×7×5 cm caudal mediastinal mass extending from the level of the right atrium to the diaphragm and surrounding the oesophagus. Total excision was achieved by a left sixth intercostal thoracotomy approach. Histological examination was consistent with a sterile abscess. The dog recovered uneventfully and was discharged on the third day after surgery. One year following surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 8 publications
1
9
0
Order By: Relevance
“…Previous reports of caudal mediastinal cysts and paraesophageal abscesses have demonstrated similar imaging findings in all affected dogs . Because of this repeatable appearance, the constancy of imaging signs may be due to some underlying anatomic reason, like involvement of the mediastinal serous cavity.…”
Section: Introductionsupporting
confidence: 61%
See 3 more Smart Citations
“…Previous reports of caudal mediastinal cysts and paraesophageal abscesses have demonstrated similar imaging findings in all affected dogs . Because of this repeatable appearance, the constancy of imaging signs may be due to some underlying anatomic reason, like involvement of the mediastinal serous cavity.…”
Section: Introductionsupporting
confidence: 61%
“…Literature review identified a single case series and five case reports describing a total of 12 dogs, 10 of which were called paraesophageal abscesses and two were called mediastinal cysts 2. [1][2][3][4][5][6] This group was comprised of three neutered males, five intact males, and four intact females. All dogs were medium-to-large breed, and three were younger than 2 years.…”
Section: Case Series Studymentioning
confidence: 99%
See 2 more Smart Citations
“…The largest veterinary case series to date reported 7 dogs, all of which were managed with a surgical approach 6 . There is an additional report reporting a successful surgery in an Irish Setter; otherwise, the literature on this condition in dogs is sparse 7 . The condition has been reported in 2 cats.…”
Section: Discussionmentioning
confidence: 99%